Effect of Cassava Flour Ratios and Binder levels on Nutritions and Physical Properties of Pellets Made from Calliandra and Lamtoro - Ayuningsih, Budi; SUSILAWATI, IIN; Indriani, Nyimas Popi; Usamah, Arkan; Rahmanosa, Elvia (Fakultas Peternakan, Universitas Padjadjaran, 2025)
AbstractFeed in the form of pellets is one form of preservation of feedstuffs that is more guaranteed in terms of procurement and continuity of supply to maintain feed quality. This study aims to determine the effect of the level of cassava flour in pellets of calliandra and lamtoro mixture as a binder on physical properties and on the content of dry matter, organic matter, and crude protein. The study used an experimental method with a completely randomized design (CRD) with 4 treatments and 5 replications. The treatments consisted of P0 (100% mixture of calliandra and lamtoro + 0% cassava flour), P1 (90% mixture of calliandra and lamtoro + 10% cassava flour), P2 (80% mixture of calliandra and lamtoro + 20% cassava flour), and P3 (70% mixture of calliandra and lamtoro + 30% cassava flour). The study showed that the treatment had a significant effect (P < 0.05) on durability (87.40% to 77.88%) and crude protein (22.33% to 16.39%) and had no significant effect (P > 0.05) on specific gravity, pile density, pile compaction density, dry matter and organic matter content. From the results of the study, it can be concluded that the P0 (100% mixture of Calliandra and lamtoro) treatment produced the highest durability and crude protein values.